From Grass to Biogas: Benefits and Challenges of a Circular Business Model - Hedegaard, Michael; Eriksen, M. Lynn; Kjærsgaard, Niels C.; Knudby, Torben; Lund, Victor; Salvador, Rodrigo (European Journal of Sustainable Development, 2025)
This paper investigates the feasibility and challenges of converting municipal grass clippings into biogas, drawing on empirical insights from the Power Bio (https://gate21.dk/projekt/powerbio/) project in Denmark and Sweden. Using field trials, stakeholder workshops, and two rounds of municipal surveys, we map the grass-to-biogas value chain and identify critical success factors and barriers to implementation. The study identifies variations in municipal practices, evaluates logistics and contamination challenges, and examines technical adaptations at biogas plants. Findings show that while biogas conversion is technically viable and environmentally beneficial, institutional fragmentation, lack of standardization and adaptive planning, logistical timing, and equipment constraints limit scalability. We outline suggestions for a business case and an action plan to support municipal integration into bioenergy systems, contributing to circular economy and climate mitigation agendas. Keywords: Environmental performance, Biogas, Grass biomass, Circular economy, Renewable energy, Municipal waste valorization